Utilization Of Information Technology For The Development Of Umkm In The People's Market In Palembang City - Fretty Welta; Sopian Sopian (Citakonsultindo, 2025)
The selection of marketing through digital media, especially social media, can be the main choice made by business actors, now the use of social media has become the main pillar in conveying information. One of the advantages of social media is that it has a lot of potential for the progress of a business. Social media can be used to communicate in business, help market products and services, communicate with customers and suppliers, complement brands, reduce costs and for online sales, therefore along with the running of the People's Market in Palembang City, it has become one of the choices for people to use digital media in making transactions to fulfill their daily needs.